Competitive advantage and sustainability in Ghanaian microfinance institutions: the mediating role of strategic capabilities - Mensah Marfo; Abiel Ashitey ARMAH; Eleazer Fianko Ofei; Isaac Sewornu Coffie; Linda Adadevoh; Sanjeet Kumar Pattnaik; Carl Asante Reindoph; Edward Annan (Future Business Journal)
Abstract This study explores the effect of competitive advantage on sustainability within Ghanaian microfinance institutions (MFIs), emphasizing the mediating role of strategic capabilities. We conducted a quantitative analysis using survey data from 500 managers representing 150 MFIs in Ghana, analyzed through structural equation modeling. Our findings indicate that competitive advantages and strategic capabilities have a positive significant influence on MFI sustainability. Additionally, strategic capabilities were found to mediate the relationship between competitive advantage and sustainability within Ghanaian MFIs. This study expands the theoretical framework by incorporating cost differentiation, pricing strategy, focus strategy, market strategy, efficient operations and risk management, innovation in product offerings, target market considerations, and client relationship management. We highlight how MFIs can maintain competitiveness through technology, partnerships, training, career development, and knowledge transfer. This mediated relationship underscores the crucial role of strategic capabilities in achieving sustainable operations. The study provides a conceptual framework for understanding MFI sustainability and offers a roadmap to enhance competitive advantage. By integrating elements from the competitive advantage theory and extending the resource-based view theory, this research contributes to the existing knowledge by clarifying the connections between competitive advantage and sustainability in the context of MFIs. Furthermore, the study addresses the dynamics of competitive advantage, strategic capabilities, and sustainability in a context with limited research. It offers practical implications for policymakers and practitioners, providing insights that can inform targeted interventions to enhance capacities and foster sustainability in the microfinance sector.